Dietary calcium intake influences the relationship between serum 25-hydroxyvitamin D3 (25OHD) concentration and parathyroid hormone (PTH) concentration. Issue 4 (10th September 2015) - Patel, Prerna; Mughal, M Zulf; Patel, Pinal; Yagnik, Bhrugu; Kajale, Neha; Mandlik, Rubina; Khadilkar, Vaman; Chiplonkar, Shashi A; Phanse, Supriya; Patwardhan, Vivek; Patel, Ashish; Khadilkar, Anuradha
Abstract : Objectives: To investigate whether dietary calcium intake will modify the relationship between serum 25-hydroxyvitamin D3 (25OHD) with intact serum parathyroid hormone (PTH) concentrations in apparently healthy Indian adolescents. Study design: Cross-sectional study. Setting and participants: Apparently healthy adolescents aged 10–14 years (n=181), from Gujarat, western India. Study conducted from January 2012 to March 2014. Methods: Serum 25OHD concentrations and intact serum PTH concentrations (both using chemiluminescent microparticle immunoassay) were measured. Diet was recorded through 24 h diet recall and calcium intake was computed (C-diet V.2.1). To assess relationship between 25OHD and PTH, data were dichotomised according to median calcium intakes (520 mg/day) and relationship between serum 25OHD and PTH in the two subgroups was plotted. Results: Subjects with calcium intakes above median (>520 mg/day) had lower intact serum PTH values for given serum 25OHD concentration while those with calcium intakes below median (<520 mg/day) had higher intact serum PTH values for given serum 25OHD concentration. Serum 25OHD concentration was negatively correlated with intact serum PTH concentration at lower as well as higher calcium intakes (r=− 0.606 and −0.483, respectively, p<0.01 for both). Using a regression analysis, predicted values for intact serum PTH concentration for the given serum 25OHD concentrations were plotted. The plot revealed a negative shift with increasing calcium intake. Conclusions: Dietary calcium intake modifies the relationship between serum 25OHD concentrations and intact serum PTH concentrations. Thus, dietary calcium intake should be taken into account when assessing an individual's vitamin D status.